Public Acceptance of Carbon Tax Implementation: A Nationwide Empirical Study in Malaysia - Izlawanie Muhammad; Norfakhirah Nazihah Mohd Hasnu; Mohd Adha Ibrahim; Suhaila Abdul Hamid; Mustafa Mohd Hanefah (UKM Press, 2024)
Indexed by MyCite